The Paradox of Visionary Leadership: Sustainability Risks in Founder-Led Biotechnology Firms - Arradina Zessa Devy; Achmad Husen; Dian Alfia Purwandari; Nurcitra Rehulina Br Ginting; Ardiyanti (Syntax Corporation Indonesia, 2025)
Visionary leadership is often regarded as the hallmark of success in modern organizations, yet it embodies a profound paradox. This study explores the tension between the inspirational power of a visionary founder and the systemic risks arising from overdependence on a singular figure in a biotechnology start-up. Employing a mixed-methods approach combining quantitative Structural Equation Modeling (SEM) analysis and narrative interpretation, this article reveals how leader-centric cultures may accelerate growth but also jeopardize long-term organizational resilience. These findings carry significant implications for organizational practice, suggesting that biotechnology firms must implement structural reforms to complement visionary leadership with robust governance frameworks and formal succession planning. The study contributes to leadership theory by challenging conventional assumptions about the universal benefits of visionary leadership and highlighting its intricate relationship with organizational sustainability. For policymakers and investors, the results emphasize the necessity of promoting governance diversification in founder-led enterprises. By bridging empirical analysis with critical humanities perspectives, this research offers novel insights into how visionary leadership shapes institutional dynamics, collective behavior, and ethical decision-making within high-growth organizations.